ÇOCUK YOĞUN BAKIMDA TRAVMA NEDENİ İLE TAKİP EDİLEN HASTALARIN KLİNİK, LABORATUVAR VE GÖRÜNTÜLEME YÖNTEMLERİNİN DEĞERLENDİRİLMESİ - KORUCUOĞLU, HAKAN (Fırat Üniveristesi, 2020)
Bu çalışmada Fırat Üniversitesi Hastanesi Çocuk Yoğun Bakım Ünitesine (ÇYBÜ) kabul edilen travmalı hastalarda klinik, laboratuvar, görüntüleme yöntemlerinin, travma skorlama sistemlerinin ve sonlanım durumunu etkileyen risk faktörlerinin değerlendirilmesi amaçlanmıştır. Fırat Üniversitesi ÇYBÜ'ye 01/01/2015 ile 01/01/2019 tarihleri arasında travma nedeniyle yatışı yapılan hastalar retrospektif olarak incelendi. Hastaların epidemiyolojik özellikleri, ÇYBÜ'ye yatış anındaki vital bulguları, fizik muayeneleri, laboratuvar değerleri, görüntüleme bulguları, 'Pediatric index of mortality-2' (PIM-2), 'Pediatric Risk of Mortality' (PRISM), Glaskow Koma skoru (GKS), Pediatrik Travma Skoru (PTS), CRAMS skorlama değerleri, yoğun bakımda ve hastanede kalış süreleri, aldığı tedaviler, sonlanım durumları retrospektif olarak incelendi. Çalışmamıza alınan 82 olgunun 47'si (%57.3) erkek, 35'i (% 42.7) kız, olguların yaş ortalaması 62±50.9 aydır. Olguların 21'inin (%25.6) ölüm ile sonlandığı, 10'unun (%12.2) kalıcı hasar ile iyileştiği, 51'inin (%62.2) tam düzelme gösterdiği saptandı. Olgular travma mekanizmaları açısından değerlendirildiğinde 32 (%39) olgu yüksekten düşme, 15 (%18.3) olgu ADTK, 14 (%17.1) olgu AİTK, 9 (%11) olgu üzerine ağır cisim düşmesi, 5 (%6.1) olgu ateşli silah yaralanması, 4 (%4.9) olgu spor yaralanması, 3 (%3.6) olgu ise bisiklet-motorsiklet yaralanması ile travmaya maruz kalmıştı. Yaş gruplarına göre travma mekanizması incelendiğinde 0-4 yaş ve 4-9 yaş grubunda yüksekten düşme, 9-15 yaş grubunda ADTK, >15 yaş grubunda AİTK en sık görülen travma mekanizmasıdır. Yaş grupları ile travma mekanizmaları arasındaki ilişki istatistiksel olarak anlamlı saptanmıştır (p<0.05). Travma mekanizmaları, sonlanım durumları açısından istatistiksel açısından değerlendirildiğinde kalıcı hasar ile anlamlı fark olmadığı, ölüm ile istatistiksel olarak anlamlı bir ilişki olduğu görüldü (p<0.05). Sonlanım durumlarına göre travma skorları değerlendirildiğinde ölüm ile sonlanımı olan hastalarda ortalama GKS 4.7±2.1, PTS -4±1.4, CRAMS skoru 3.2±1.6, PIM-2 skoru % 91.24 ±20.34, PRISM skoru 82.31±16.41'dir. GKS, PTS, CRAMS skoru düşük olan, PIM-2, PRISM skoru ise yüksek olan olgularda ölüm ile sonlanım daha fazla görüldü. Skorlama sistemleri mekanik ventilatör desteği alan ve almayan hastalarda karşılaştırıldığında istatistiksel olarak anlamlı bulundu (p<0.05). İstatistiksel olarak değerlendirildiğinde travma skorları ile sonlanım durumu açısından anlamlı bir ilişki olduğu görüldü (p<0.05). Travma skorlama sistemlerine bakıldığında GKS, PTS derecesinin ağır olması ve CRAMS skorunun ciddi olması ile sonlanım durumu arasında istatistiksel olarak anlamlı ilişki saptanmıştır (p<0.05). Olguların yoğun bakım ünitesinde almış oldukları tedaviler değerlendirildiğinde 29 (%35.4) olgunun inotrop, 36 (%43.9) olgunun kan transfüzyonu, 44 (%53.6) olgunun mekanik ventilasyon desteği ihtiyacı olmuşken, 20 (%24.4) olgunun cerrahi tedavi gereksinimi mevcuttu. Sonlanım durumlarına göre değerlendirildiğinde kan transfüzyonu, mekanik ventilatör, inotrop ve cerrahi ihtiyacı olan olgularda ölüm oranı daha yüksek olup istatistiksel olarak anlamlıdır (p<0.05). Kalıcı hasar açısından değerlendirildiğinde cerrahi işlem uygulanan hastalarda morbidite daha yüksek olup istatistiksel olarak anlamlı bulunmuştur (p<0.05). Çocuk Yoğun Bakımda travmalı hastalarda ölümler en sık yatışın ilk 24 saati içinde olmuştur. Travmalı hastalara yapılacak ilk müdahale sonlanım için önem arz etmektedir. Travma hastasına multidisipliner yaklaşım ve hızlı müdahale şarttır. Travmalı hastaların ilk karşılandığı acil servislerde travma konusunda tecrübeli çocuk doktoru, çocuk cerrahı, ilgili cerrahi branşlar, travma konusunda tecrübeli hemşire ve diğer sağlık çalışanlarının bulunduğu travma ekiplerinin kurulmasının bu hastalara müdahalede başarı oranını arttıracağı düşünülmektedir. Anahtar kelimeler: ÇYBÜ, travma, mortalite, travma skorlama sistemleri, çocuk

In this study, it was aimed to assess clinical, laboratory, imaging methods, trauma scoring systems and risk factors affecting the outcome of trauma patients admitted to Firat University Hospital Pediatric Intensive Care Unit. Patients who were admitted to Firat University Hospital Pediatric Intensive Care Unit (PICU) between 1 January 2015 and 1 January 2019 due to trauma were retrospectively examined. Epidemiological characteristics of patients, vital findings during the hospitalization, physical examinations, laboratory assessments, imaging findings, 'Pediatric index of mortality-2' (PIM-2), 'Pediatric Risk of Mortality' (PRISM), Glasgow Coma Scale (GCS), Pediatric Trauma Score (PTS), CRAMS scale, duration of stay in the intensive care unit and length of hospital stay, treatments received and outcome conditions were analysed and examined retrospectively. From the 82 cases included in our study, 47 (57.3%) were male, 35 (42.7%) were female, and the mean age of the patients/cases was 62±50.9 months. It was observed that 21 (25.6%) of the cases resulted in death, 10 (12.2%) recovered with permanent damage, 51 (62.2%) showed complete recovery. When the cases are assessed in terms of trauma mechanisms, 32 (39%) cases were exposed to trauma due to falling down from height, 15 (18.3%) cases were exposed to trauma due to extravehicular traffic accident, 14 (17.1%) cases were exposed to trauma due to in-vehicle traffic accident, 9 (11%) cases were exposed to trauma due to falling heavy object, 5 (6.1%) cases were exposed to trauma due to firearm injuries, 4 (4.9%) cases were exposed to trauma due to sports injuries, 3 (3.6%) cases were exposed to trauma due to bicycle-motorcycle injuries. When trauma mechanisms were examined according to the age groups, falling down from the height in the 0-4 age group and 4-9 age group, extravehicular traffic accident in the 9-15 age group and in-vehicle traffic accident in the >15 age group are the most common trauma mechanisms. The relation between age groups and trauma mechanisms was found statistically significant (p<0.05). When trauma mechanisms were assessed statistically in terms of outcome conditions, it was determined that there was no significant difference with permanent damage, and there was significant relation with death statistically (p<0,05). When trauma scores are assessed according to the outcome conditions, the average Glasgow Coma Scale (GCS) is 4.7±2.1, Pediatric Trauma Score (PTS) is 4±1.4, CRAMS Scale is 3.2±1.6, Pediatric index of mortality (PIM-2) scale is 91.24 ±20.34 % and Pediatric Risk of Mortality (PRISM) scale is 82.31±16.41% in the outcome of patients resulted in death. In cases with low Glasgow Coma Scale (GCS), Pediatric Trauma Score (PTS), CRAMS scale and in cases with high Pediatric index of mortality (PIM-2) scale, Pediatric Risk of Mortality (PRISM) scale, it was observed that outcome resulted in death were more common. Scoring systems were found statistically significant when compared with patients with and without mechanical ventilation support (p<0.05). When assessed statistically, it was observed that there was a significant relation between trauma scores and outcome conditions (p<0.05). Considering the trauma scoring systems, there was a statistically significant relation between severe Glasgow Coma Scale (GCS) and Pediatric Trauma Score (PTS), and severe CRAMS scale and outcome conditions (p<0.05). When the treatments received in the intensive care unit were assessed, 29 (35.4%) cases required inotrope, 36 (43.9%) cases required blood transfusion, 44 (53.6%) cases required mechanical ventilation support, and 20 (24.4%) cases required surgical treatment. Considering the outcome conditions, the mortality rate is higher and statistically significant in cases required blood transfusion, mechanical ventilation, inotrope and surgery (p<0.05). When assessed in terms of permanent damage, morbidity was higher and found statistically significant in patients who underwent surgery (p<0.05). Mortalities in patients with trauma in the pediatric intensive care unit were most frequently occurred within the first 24 hours from hospitalization. The first medical intervention to trauma patients is important for outcome. The multidisciplinary approach and quick intervention is essential for the trauma patient. It is considered that the establishment of trauma teams including experienced pediatrician, pediatric surgeon, nurses and healthcare professionals about trauma and relevant surgical specialities in the emergency departments where trauma patients are first admitted to the hospital will increase the success rate in medical intervention to these patients. Key words: PICU, trauma, mortality,trauma scoring systems, child
Evaluation of clinical, laboratory and imaging methods of patients monitored due to the trauma in pediatric intensive care unit
Keywords: Çocuk Sağlığı ve Hastalıkları